Lusitana 3 amphora in Lusitania: resampling the commerce and consumption of Lusitanian wine production - Filipe , Victor; Roberto de Almeida , Rui (Rei Cretariae Romanae Fautorum Acta, 2024)
Although they have been characterized for decades, there is still lack of knowledge about the relevance of the Lusitana 3 type in the Lusitanian wine trade. A recent study of the amphorae of Olisipo (Lisbon), where Lusitana 3 are dominant among the wine containers, has highlighted the great development of wine production in the Tagus Valley during the 2nd and 3rd centuries AD. At the same time, the importance of this amphora type, with evident Gaulish influences, is noticeable in the wine trade of the province. However, this relevance is less recognizable throughout the remaining territory of Lusitania. The present study, which is based on the analysis of amphorae assemblages from several consumption sites in Lusitania, focuses on the Lusitanian wine trade and highlights the importance of the Lusitana 3 amphora in this context.